INTEGRATSIYALASHGAN TA’LIM TUSHUNCHASI VA UNING PEDAGOGIK MOHIYATI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article provides a comprehensive analysis of the concept of integrated education, its theoretical foundations, pedagogical essence, and role in the modern educational system. The didactic, methodological, and psychological aspects of integrated education are examined, highlighting its potential to develop learners’ knowledge, skills, and competencies through interdisciplinary connections. Based on scholarly sources, the types and stages of integration and mechanisms for its implementation in the educational process are discussed. The relationship between integrated education, learner-centered approaches, competency-based education, and innovative pedagogical technologies is substantiated. The findings contribute to improving educational effectiveness and fostering systemic thinking among learners.